On the toxicity and transport mechanisms of cisplatin in kidney tissues in comparison to a gold-based cytotoxic agent. Issue 12 (6th November 2017) - Spreckelmeyer, Sarah; Estrada-Ortiz, Natalia; Prins, Gerian G. H.; van der Zee, Margot; Gammelgaard, Bente; Stürup, Stefan; de Graaf, Inge A. M.; Groothuis, Geny M. M.; Casini, Angela
Abstract : The toxic effects and accumulation mechanisms of cisplatin in healthy rat kidneys has been studied ex vivo, using the Precision Cut Tissue Slices (PCTS) method, in comparison to those exerted by an experimental cytotoxic Au(iii ) compound. Abstract : Mechanisms of toxicity and cellular transport of anticancer metallodrugs, including platinum-based agents, have not yet been fully elucidated. Here, we studied the toxic effects and accumulation mechanisms of cisplatin in healthy rat kidneys ex vivo, using the Precision Cut Tissue Slices (PCTS) method. In addition, for the first time, we investigated the nephrotoxic effects of an experimental anticancer cyclometallated complex [Au(py b -H)(PTA)Cl]PF6 (PTA = 1, 3, 5-triazaphosphaadamantane). The viability of the kidney slices after metallodrug treatment was evaluated by ATP content determination and histomorphology analysis. A concentration dependent decrease in viability of PCKS was observed after exposure to cisplatin or the Au(iii ) complex, which correlated with the increase in slice content of Pt and Au, respectively. Metal accumulation in kidney slices was analysed by ICP-MS. The involvement of OCTs and MATE transporters in the accumulation of both metal compounds in kidneys was evaluated co-incubating the tissues with cimitedine, inhibitor of OCT and MATE. Studies of mRNA expression of the markers KIM-1, villin, p53 and Bax showed that cisplatin damages proximal tubules, whereas the Au(iii ) complex preferentially affects the distal tubules. However, no effect of cimetidine on the toxicity or accumulation of cisplatin and the Au(iii ) complex was observed. The effect of temperature on metallodrug accumulation in kidneys suggests the involvement of a carrier-mediated uptake process, other than OCT2, for cisplatin; while carrier-mediated excretion was suggested in the cases of the Au(iii ) complex.